Potential mitigation of climate change from the adoption of new habits in São Paulo city - Brazil - Kuroki, Larissa Yumi (2024)
Regarding climate change, not only government and business actions are part of its mitigation, but civil behaviors aimed at low-carbon lifestyles are essential. Thus, this work aims to estimate the potential reduction of the carbon footprint of a São Paulo citizen from the adoption of behavioral changes. Through a bibliographic review and the use of life cycle inventory tools, data were collected on the intensity of consumption of products and services by São Paulo residents and their respective GHG emissions, and interviews were conducted with the population to define behaviors capable of reducing the city's carbon footprint. The results showed that direct consumption reduction practices, such as energy savings, are more viable and that the potential reduction of the carbon footprint for a São Paulo citizen is 46.87% - that is, this percentage reflects the difference between the footprint of current and reduced average carbon of São Paulo residents, respectively estimated as 4.16 and 2.2 tCO2e/year. The current carbon footprint of São Paulo residents is similar to the global average (4.0 tCO2e/cap.year), but there is a need to adopt less carbon-intensive habits to meet the Paris Agreement goal of keeping the planet's temperature rise at 2°C by 2100. To do so, the average global carbon footprint must be reduced to 2.0 tCO2e/cap.year by 2050, and this study estimated that, if new behaviors are adopted, the carbon footprint of a São Paulo citizen can be reduced to 2.2 tCO2e/cap.year.